2021
DOI: 10.3389/fendo.2021.655197
|View full text |Cite
|
Sign up to set email alerts
|

Hair Cortisol Concentration, Weight Loss Maintenance and Body Weight Variability: A Prospective Study Based on Data From the European NoHoW Trial

Abstract: Several cross-sectional studies have shown hair cortisol concentration to be associated with adiposity, but the relationship between hair cortisol concentration and longitudinal changes in measures of adiposity are largely unknown. We included 786 adults from the NoHoW trial, who had achieved a successful weight loss of ≥5% and had a body mass index of ≥25 kg/m2 prior to losing weight. Hair cortisol concentration (pg/mg hair) was measured at baseline and after 12 months. Body weight and body fat percentage wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…The longitudinal changes in cortisol levels were also negatively associated with these measures of adiposity [ 62 ]. Hair cortisol levels are proposed as one of the ways to measure chronic stress levels, that differ from the urinary, blood or salivary cortisol [ 63 ]; however, Larsen et al found no association between the hair cortisol levels and weight loss maintenance in patients that had achieved a significant weight loss [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…The longitudinal changes in cortisol levels were also negatively associated with these measures of adiposity [ 62 ]. Hair cortisol levels are proposed as one of the ways to measure chronic stress levels, that differ from the urinary, blood or salivary cortisol [ 63 ]; however, Larsen et al found no association between the hair cortisol levels and weight loss maintenance in patients that had achieved a significant weight loss [ 64 ].…”
Section: Introductionmentioning
confidence: 99%